“Wesley says”: a children’s response inhibition playground training game yields preliminary evidence of transfer effects - Zhao, Xin; Chen, Ling; Fu, Lily; Maes, Joseph H. R. (Frontiers in Psychology, 2015)
Recent studies suggest that the response inhibition ability of children can be modified through training. Based on the notion of embodied cognition, we investigated transfer effects of a 7-day training program using a game named “Wesley says” in 8- to 12-year-old children (n = 15). The game consists of providing commands for performing simple body actions, the actual execution of which is conditional upon the preceding verbal expression “Wesley says.” Training effects were assessed with a computer-based visual go/no-go task and the Stroop color–word interference task. Relative to a control group playing other games mainly involving physical exercise (n = 15), the trained group showed a performance improvement on the go/no-go task, but not on the Stroop task. These results suggest the potential of an easy-to-use and ecologically valid training game to improve the inhibition capacity of children on related response inhibition tasks but not on tasks measuring other aspects of inhibition, such as interference control.